Portuguese Society of Gastroenterology Consensus on the Diagnosis and Management of Hemorrhoidal Disease - Salgueiro, Paulo (2020)
Hemorrhoidal disease (HD) is a frequent health problem with considerable repercussions on patients' quality of life. However, much of the clinical practice related to HD is based on knowledge without scientific evidence and supported largely by empirical experience of the physician who deals with this pathology. As in other countries, the goal of this consensus is to establish statements supported by solid scientific evidence and whose purpose will be to standardize and guide the diagnosis and management of HD both in the general population and in some particular groups of patients.